Condicionantes sócio-históricos das políticas públicas no ensino médio: entre o profissional e o propedêutico - Silveira, Everton de Paula (Universidade Federal de São Carlos, 2014)
This paper investigates the historical and social factors that characterize the context of public policy high school in Brazil aimed at training the student in meeting the demands of the labor market. Examines the theoretical assumptions that underlie the relationship between work and schooling and its implications for the definition of norms governing national education, with consequent unfolding develop national curriculum guidelines for high school. Through a literature search based on historical materialism sought to understand the factors that affect the organization of social life from the implications of the industrial revolution in the world of work and, consequently, the school as an area for preparing the young for their inclusion in productive life. The analysis of the legal rules governing the organization and provision of secondary education and the national curriculum guidelines for this stage of basic education , allows us to understand the concepts that has been based on the development of norms of education in the country and the interests behind the political public education, largely subject to the recommendations of international organizations, which have assigned the task of education to equalize social inequalities, favoring economic development of nations. The study demonstrated that it is not possible to think about the role of education in preparing students for the job, regardless of the changes occurring in the social organization of work, caused mainly by changes in the system of capitalist production, suggesting the need to rethink the high school beyond its preparatory or professional character, through the possibility of developing an educational policy that believes and promotes the formation of an integrated high school student teaching.
Socio and historical conditions of public policy in high school: between the professional and preparatory
Keywords: Educação e Estado; Education and state; Educação para o trabalho; Career education; Ensino médio; High School; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO